Pelatihan Hospitality dan Budaya Jepang bagi Pelaku Pariwisata di Desa Jatiluwih - Andriyani, Anak Agung Ayu Dian; Ardiantari, Ida Ayu Putri Gita; Sulatra, I Komang (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2024)
Tourism is an important sector in the economy of Jatiluwih Village, and visits by Japanese tourists have become a potential market that has been increasing in recent years. However, to improve the quality of service for Japanese tourists which indirectly can expand market share, tourism actors need to have adequate knowledge of the culture, customs and habits of Japanese people as well as the ability to communicate using basic Japanese, with the aim of providing the best service. Post-pandemic, the world of tourism has revived. To revive work enthusiasm and service attitude to Japanese tourists, the role of the university is needed to help provide knowledge and skills to tourism actors when communicating with tourists of different cultures, therefore misunderstandings can be avoided in communication. One of the efforts to increase the knowledge and skills of tourism actors in Jatiluwih Village, required hospitality and Japanese culture training. This training involved experts who have experience in the tourism industry and expertise in Japanese culture. Through this training, it was hoped that tourism actors will gain in-depth knowledge of Japanese culture, including language, customs, and the ethics of interacting with Japanese tourists. They were also trained in hospitality skills which include communication, hospitality, service skills, and understanding of Japanese guest preferences.